Dupilumab-Associated Mycosis Fungoides with a CD8+ Immunophenotype - Ariel Park; Lulu Wong; Annalise Lang; Christina Kraus; Nancy Anderson; Ashley Elsensohn (MDPI AG, 2022)
Dupilumab is a humanized IgG4 monoclonal-antibody that is approved by the United States Food and Drug Administration (FDA) for the treatment of moderate-to-severe atopic dermatitis (AD) in patients aged 12 years and older. In recent years, several case studies have associated the unmasking or progression of cutaneous T-cell lymphomas (CTCL) with dupilumab treatment. To date, all reported cases of dupilumab-associated CTCL have shown a CD4+ T-helper-cell-predominant immunophenotype. Here, we report a case of a 72-year-old man who presented with a 2-year history of a diffuse, pruritic eruption, who was started on dupilumab for 9 weeks. He subsequently developed mycosis fungoides (MF) with a CD8+-predominant immunophenotype. Overall, cases of CD8+ mycosis fungoides are less common and relatively less understood than their CD4+ counterparts, with varied presentations and courses. We present a case of dupilumab-associated CD8+ MF to highlight this presentation for pathologists and providers.